Numerical study on hydrodynamic resistance of new hull design for multipurpose amphibious vehicle - Abdul Malek, Adi Maimun (2013)
Multipurpose Amphibious Vehicles (MAV) and other blunt-shaped floating vehicles encounter the problem of a large bow wave forming at high speeds. This wave formation is accompanied by higher resistance and at a critical speed results in bow submergence or swamping. Three new shapes of hull bow design for the multipurpose amphibious vehicle were conducted at several speeds to investigate the hydrodynamic phenomena using Computational Fluid Dynamics (CFD, RANS code) which is applied by Ansys-CFX14.0 and Maxsurf. The vehicle’s hydrodynamic bow shapes were able to break up induced waves and avoid swamping. Comparative results with the vehicle fitted with U-shape, V-shape and Flat-shape of hull bow, showed that the U-shape of the hull bow has reduced the total resistance to 20.3% and 13.6% compared with the V-shape and flat shape respectively. Though, the U-shape of hull bow is capable to increase the amphibious operating life and speed of vehicle. Also it has ability to reduce the vehicle’s required power, fossil fuel consumption and wetted hull surface.